Teaching cause-of-death certification: lessons from international experience. Issue 1013 (17th March 2010) - Aung, Eindra; Rao, Chalapati; Walker, Sue
Abstract : Background and objective: The accuracy of cause-of-death statistics substantially depends on the quality of cause-of-death information in death certificates, primarily completed by medical doctors. Deficiencies in cause-of-death certification have been observed across the world, and over time. Despite educational interventions targeted at improving the quality of death certification, their intended impacts are rarely evaluated. This review aims to provide empirical evidence that could guide the modification of existing educational programmes, or the development of new interventions, which are necessary to improve the capacity of certifiers as well as the quality of cause-of-death certification, and thereby, the quality of mortality statistics. Design: A literature review using keywords: death; certification; education/training. Data sources: The primary search through PubMed. Reference lists in individual articles from the primary search and also manual searching of other databases such as Google Scholar and OpenDOAR. Eligibility criteria for selecting studies: Evaluation studies which assessed educational interventions for medical students and doctors on correct completion of death certificates. Results: All educational interventions identified in this review improved certain aspects of death certification although the statistical significance of evaluation results varies with the type of intervention: printed educational material alone being the intervention with the least educational impact and interactive workshops being the most effective intervention. Conclusions: Pragmatic education on best practice for cause-of-death certification is a basic step to ensure accurate information for each individual case, leading to the production of high quality mortality statistics for epidemiology, public health policy and research. Development of new educational interventions or modification of existing programmes should be based on evidence of the benefits from current and past interventions provided under varying circumstances.